2021
DOI: 10.3389/fvets.2021.628389
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Commercial Glanders ELISA as an Alternative to the CFT in International Trade of Equidae

Abstract: Glanders, caused by Burkholderia (B.) mallei is a notifiable zoonotic disease in equidae. For international trade and movement of equids, certificates of negative serological test results for antibodies against B. mallei are required. To date, the complement fixation test (CFT) is the mandatory test to issue these health certificates. The CFT is difficult to standardize and, due to its poor specificity, often leads to false-positive reactions resulting in trade restrictions with considerable financial conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 24 publications
(19 reference statements)
0
22
0
Order By: Relevance
“…2 and 3 and confirmed by statistical analysis (Table S4), 12 out of 22 protein antigens (BPSS1498, BPLS2697, BPSS0477, BPSS1840, BPSL2522, BPSL2096, BPSS2141, BPSL1445, BPSL2698, BPSS0476, BPSL2520, BPSS1532) differed significantly between sera from panel P1 and control sera from panels P2 and P3. The highest signal intensities on average were obtained for BPSS1498 (Hcp1), BPSL2697 (molecular chaperone GroEL1), and BPSS0477 (molecular chaperone GroEL2), proteins of interest that have already been mentioned for glanders ( 17 , 19 , 20 ), but also for new proteins described in our study, such as BPSS1840 (putative N -acetylmuramoyl- l -alanine amidase), BPSL2522 (outer membrane protein A precursor), and BPSL2096 (putative hydroperoxide reductase).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…2 and 3 and confirmed by statistical analysis (Table S4), 12 out of 22 protein antigens (BPSS1498, BPLS2697, BPSS0477, BPSS1840, BPSL2522, BPSL2096, BPSS2141, BPSL1445, BPSL2698, BPSS0476, BPSL2520, BPSS1532) differed significantly between sera from panel P1 and control sera from panels P2 and P3. The highest signal intensities on average were obtained for BPSS1498 (Hcp1), BPSL2697 (molecular chaperone GroEL1), and BPSS0477 (molecular chaperone GroEL2), proteins of interest that have already been mentioned for glanders ( 17 , 19 , 20 ), but also for new proteins described in our study, such as BPSS1840 (putative N -acetylmuramoyl- l -alanine amidase), BPSL2522 (outer membrane protein A precursor), and BPSL2096 (putative hydroperoxide reductase).…”
Section: Resultsmentioning
confidence: 62%
“…The following three panels of equid sera were included in this study: P1, 30 positive sera from clinically confirmed glanders cases from Pakistan, where the disease is endemic; P2, 14 control sera of horses infected with pathogens other than B. mallei (dourine [ n = 3], equine metritis [ n = 5], equine infectious anemia [ n = 2], and viral arthritis [ n = 4]), provided by the European Reference Laboratory for Equine Diseases; and P3, 39 sera of healthy controls obtained from officially glanders-free countries (France [ n = 7], Ireland [ n = 3], and Tunisia [ n = 29]). In agreement with previous studies, horses showing clinical signs related to glanders were regarded glanders cases if they were positive in a serological assay (CFT, indirect ELISA [iELISA]) or in close contact with glanders-positive horses during culture-confirmed outbreaks ( 19 , 20 ). No ethical approval was required for this study because field sera from the P1, P2 and P3 panels were collected for monitoring and diagnostic purposes.…”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…Alternative serological tests based on B. mallei protein extracts or recombinant proteins have been developed and recent comparison studies concluded that sensitivity and specificity of evaluated tests were comparable with those obtained with the complement fixation test, opening the possibility of replacing it by more easily standardisable methods (Elschner et al, 2017(Elschner et al, , 2021. Nevertheless, one of the current constraints for ELISAs is their availability in a commercial format.…”
Section: Clinical Signs and Diagnosismentioning
confidence: 99%
“…Sera from these five equids were analyzed with five different serological tests: (i) CFT [ 6 ], (ii) ID Screen® Glanders indirect ELISA (IdVet, France) [ 7 ], (iii) GLANDA ELISA (IdVet, France) based on two recombinant proteins [ 8 ], (iv) Luminex® bead-based assay targeting Hcp1 and GroEL proteins [ 9 ], and (v) ELISA based on a glycoengineered protein of Burkholderia recently validated for glanders diagnosis (Glyco ELISA) [ 10 ]. Two horses (L/157, B/120) and one mule (B/113) were positive by all tests and positive or undetermined results were obtained for all animals with ID Screen® Glanders indirect ELISA , GLANDA ELISA and Luminex® tests.…”
Section: Introductionmentioning
confidence: 99%